The Effect of Degree of Convergence to IFRS and Governance System to Accounting Conservatism: Evidence From Asia - RATNA WARDHANI (The Indonesian Journal of Accounting Research, 2013)
Motivated by increasing pressure for full convergence to IFRS, I investigate the effect of degree of convergence from local standards to IFRS on accounting conservatism. I also examine the impact of governance system, both at country and firm level, on conservatism. This research's sample covers a number of East and South East Asia countries: Hong Kong, India, Indonesia, Japan, Korea, Malaysia, Philippines,Singapore, Taiwan and Thailand. This study concludes that the degree of convergence positively affects accounting conservatism. Governance system, both at country level and firm level, also has positive influence on accounting conservatism. Interestingly, the influence of the extent of convergence of local GAAP to IFRS and corporate governance practice on conservatism is stronger for companies in countries with weak investor protection. In addition, I find that the adoption of international standards will increase accounting conservatism in companies with weak corporate governance practice.